The relationship between rewards and teachers' motivational orientations towards professional development - D'Silva, Mary Lourett Philo (1997)
This study examined the relationship between rewards and teachers' motivational orientations towards professional development. A three-part questionnaire was used in this study. Part 1 consisted of questions relating to socio-demographic details. Part 2 consisted of questions designed to assess the motivational orientations of the teachers participating in this study. The questions in Part 3 determined which rewards were important to the teachers. Two hundred and twenty-seven school teachers from the district of Puchong served as the population of the study.